If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(1 + 3) = -1 + 2(t + -3) Combine like terms: 1 + 3 = 4 5 + -1(4) = -1 + 2(t + -3) Multiply -1 * 4 5 + -4 = -1 + 2(t + -3) Combine like terms: 5 + -4 = 1 1 = -1 + 2(t + -3) Reorder the terms: 1 = -1 + 2(-3 + t) 1 = -1 + (-3 * 2 + t * 2) 1 = -1 + (-6 + 2t) Combine like terms: -1 + -6 = -7 1 = -7 + 2t Solving 1 = -7 + 2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2t' to each side of the equation. 1 + -2t = -7 + 2t + -2t Combine like terms: 2t + -2t = 0 1 + -2t = -7 + 0 1 + -2t = -7 Add '-1' to each side of the equation. 1 + -1 + -2t = -7 + -1 Combine like terms: 1 + -1 = 0 0 + -2t = -7 + -1 -2t = -7 + -1 Combine like terms: -7 + -1 = -8 -2t = -8 Divide each side by '-2'. t = 4 Simplifying t = 4
| y/2+5/2=y/4 | | -728-4(-3)= | | 2(x-7)-3x=8+3(2-4x) | | -42= | | 9x=4y+36 | | -1(2x-3)=-2 | | 4x-108/x^2 | | 3/8+9/8=31/8 | | 1-x/5=9 | | 109+(-96)+(-45)+26= | | (2/9)/(5/9) | | 4(x-6)-2(x-3)+9x= | | 90-2x=43x+20 | | 42/3+(-6)= | | -3(7-3)+6= | | 3x^2-17m+14=0 | | -3(7-3x)+6= | | 3-(-2x-3)-5x+2=20 | | 36-4c-3c=20 | | 9z^4+87z^2+100=0 | | 6-m-6=7m+9-m | | 4+(-8)(-19)= | | 18x^4+24x^2-24=0 | | (x+6)(x-5)(3x-7)=0 | | 16y^2-80=0 | | 1/3x^2-7=-4 | | 75.6=7.2r | | (2x-6)(2x-6)=23 | | -27t^2-18t-3=0 | | 1.5*6= | | 5x+10-5=0 | | (-1/5)=x+(2/5) |